Improving the Quality of Innovation Management Learning Through Project-Based Learning Methods - Susi Damayanti (CV. AFDIFAL MAJU BERKAH, 2022)
In the learning process, the appropriate combination of the learning model used and the participation of the parties involved in learning were expected to be able to create an appropriate quality of learning, in this case according to the invasion management course. The method used was classroom action research and using SPSS, especially to find out any changes before the use of the method and after the use of the method. The stages of classroom action research were planning, implementing actions, making observations using various research instruments used, and reflections used as evaluations. The results of this study were an increase in learning outcomes from pre-cycle, cycle 1 and to cycle 2. From class 4A pre-cycle of 77.7 increased in cycle 2 to 91.5; class 4B pre-cycle of 73.6 increased in cycle 2 to 92.4; class 4C pre-cycle of 72.8 increased in cycle 2 to 91; and pre-cycle 4D class of 74.0 increased in cycle 2 to 92.3. Furthermore, from the results of the SPSS calculation for classes 4A, 4B, 4C, and 4D, the results obtained were partial, each with the same result, they were the value of Sig. (2-tailed) 0.000 < 0.05 so there was a difference before and after the use of project-based learning methods in innovation management courses.